The effect of adding cisatracurium versus hyaluronidase to levobupivacaine and lidocaine mixture in single injection peribulbar block for cataract surgery - Mohamed M. Abu Elyazed (Egyptian Journal of Anaesthesia, 2017)
Background: Several adjuvants can be utilized to improve the quality of peribulbar block (PBB). We compared the effects of adding cisatracurium or hyaluronidase to levobupivacaine and lidocaine mixture for PBB on the onset of globe and lid akinesia in cataract surgery. Methods: 105 adult patients scheduled for cataract surgery under PBB were randomly allocated into three groups. Control group received 4 ml 0.5% levobupivacaine plus 3 ml 2% lidocaine diluted in saline to a total volume of 8 ml. Hyaluronidase 15 IU/ml and cisatracurium 1 mg were added to local anesthetics (LAs) mixture in hyaluronidase and cisatracurium groups respectively. Onset and duration of lid and globe akinesia, time for adequate conditions to start surgery and adverse events were recorded. Distribution of LAs solution was evaluated by B-scan ultrasound at 3 min and 10 min after injection of LAs. Results: Onset of lid and globe akinesia, as well as time to adequate conditions to start surgery, were faster in cisatracurium and hyaluronidase groups compared to the control group (P < 0.05). Cisatracurium group had the fastest onset. At 3 min after injection of LAs, the ultrasound examination revealed that hyaluronidase group had the highest percentage of patients showing intraconal diffusion of LAs solution with the appearance of a characteristic T sign (P < 0.05). Conclusions: The addition of cisatracurium 1 mg or hyaluronidase 15 IU/ml to levobupivacaine and lidocaine mixture for PBB hastened the onset of lid and globe akinesia without increase the incidence of adverse effects. This effect is more obvious with cisatracurium compared to hyaluronidase.